Investigating plankton size spectra, biomass, abundance, and community composition in the Subtropical Convergence Front in the Southern Ocean - Yingling, Natalia; Selph, Karen E.; Décima, Moira; Safi, Karl A.; Gutiérrez-Rodríguez, Andrés; Fender, Christian K.; Stukel, Michael R. (Frontiers in Marine Science, 2025)
Phytoplankton community structure is crucial to pelagic food webs and biogeochemical processes. Understanding size-based biomass distribution and carbon dynamics is essential for assessing their contributions to oceanic carbon cycling. This study quantifies plankton carbon (C) based size spectra, community composition, living to total particulate organic carbon (POC) and C:Chlorophyll a (C:Chla) ratios across biogeographical provinces in the Pacific sector of the Southern Ocean near the Subtropical Front (Chatham Rise, Aotearoa-New Zealand). We analyzed phytoplankton community composition using epifluorescence microscopy and flow cytometry, while quantifying size-fractionated Chl-a and POC to estimate normalized biomass, abundance size spectra, and C:Chla ratios. On average, subtropical-influenced waters had lower macronutrients, higher total Chla (1.1 ± 0.2 μg Chla L-1) and were dominated by nanoplankton, which accounted for 45% of the total plankton community (35.2 ± 4.6 μg C L-1). In contrast, picoplankton dominated plankton communities within the subantarctic-influenced and accounted for 35% of the total plankton community (18.5 ± 0.9 μg C L-1) in these water with higher macronutrient concentrations and lower total Chla concentrations (0.32 ± 0.06 μg Chla L-1). Subantarctic-influenced regions had steeper (more negative) slopes for the normalized biomass size spectrum (average = -1.00) compared to subtropical-influenced waters (average = -0.78) indicating greater relative dominance of small taxa. The subantarctic-influenced region had ~2-fold higher surface average C:Chla ratios compared to the subtropical-influenced region with picoplankton consistently having lower C:Chla ratios, due to low Chla values, than larger nano- or microplankton. Live plankton carbon contributed a median of 67% of total particulate organic carbon in the euphotic zone (non-living detritus comprises the remaining ~1/3), which is indicative of substantial primary production and rapid recycling by a strong microbial loop. Our study provides important insights into phytoplankton community structure, biomass distribution and their contribution to carbon sequestration in this region, highlighting the important roles of nanoplankton in subtropical productive waters and picoplankton in offshore subantarctic waters as well as a strong variation of C:Chla across different phytoplankton size classes.